System transformation and environmental policy: Problems and options in Central and Eastern Europe - Maria J. Welfens (Intereconomics, 1993)
The economies of Central and Eastern Europe have inherited serious burdens of environmental pollution, while their economic scope for dealing with these is limited. The transition to the market economy offers chances for improvement, but it also brings new environmental problems. How will the transforming countries be able to cope?
Keywords: 330; Environmental Policy